Herramientas tecnológicas para la comprensió lectora en el área de lengua y literatura, para estudiantes de octavo año de educacion general básica paralelo “A” en la unidad educativa san pedro de Guanujo, durante el año 2022 - Guamán Azogue, Stalin Alexander (2022)
The starting point in this project was to inquire about the innovation of some technological tools that allow to improve and reinforce reading comprehension in the students of eighth year of General Basic Education parallel "A", of the Educational Unit "San Pedro de Guanujo", this technological resource, possesses an approach of scientific character, due to, that can be used for multiple areas of study. The research project had a quantitative approach, in which the survey technique was used and the questionnaire was used as an instrument, which consisted of 9 questions addressed to eighth grade students of the "San Pedro de Guanujo" Educational Unit. The method used in this research was experimental, inductive and deductive. The universe taken into account was 14 students, who were in the eighth year of General Basic Education of the aforementioned educational unit. The information collected through the survey made it possible to observe the ways in which students in the eighth year of General Basic Education carry out their reading processes, as well as to identify the technological tools used for the improvement of reading comprehension, so that they can be used to strengthen the learning processes. To conclude, it was possible to demonstrate that the application and development of the activities in the technological tool EDUCAPLAY, through its characteristics which are: to encourage interaction and participation, in which it allows the development of key competences in a fast and active way through the use of gamification, both its own and its wide repository of activities in the strengthening of the students' reading comprehension, are an optimal means to support the students' reading comprehension process.